Nodulation and Nitrogen Fixation of Pongamia pinnata - Calica, Phoebe N. (Journal of Tropical Crop Science, 2017)
Nitrogen is one of the most important nutrients required by plants as a major component of all nucleic acids and proteins such as enzymes which control and enable their growth and reproduction. While much research has been conducted on the legume tree Pongamia (a candidate source for renewable biofuel), there is only a handful of studies on the mechanisms and regulation of nitrogen fixation, which is considered as one of the most important domestication traits that needs to be investigated.  Steps to optimize the symbiotic nitrogen fixation of Pongamia is, firstly, to select the best rhizobial isolates as inoculum among the naturally-occurring pool of bacteria in soils across Queensland. There have been reports on rhizobia nodulating Pongamia isolated from Western Australia and India but not in Queensland, Australia. This study is the first to report such rhizobia isolates that nodulated Pongamia.  Secondly, is to establish efficient nodulation by studying the factors such as nitrate and salinity. The published literature has provided extensive details on the effects of these factors in nodulation and their mechanisms in various legumes. However, only one preliminary study was published from our laboratory; the present study is the in-depth continuation of that effort. Lastly, nitrogen fixation in Pongamia must be assessed to determine if fixed nitrogen is sufficient to support its growth and reproduction. Acetylene reduction assay is the simplest and most common method of assessing fixed nitrogen but in this research, different methods were explored in order to compare both qualitative and quantitative results. This review summarises the current knowledge related to Pongamia, rhizobia, nodulation and nitrogen fixation.